Spatial transcriptomics reveals tumor microenvironment heterogeneity in EBV positive diffuse large B cell lymphoma - Mei-yao He; Meng Liu; Jiayin Yuan; Jin Lv; Wei Li; Qianwen Yan; Yujiao Tang; Luyi Wang; Li Guo; Fang Liu (Scientific Reports)
Abstract Accumulating research suggests that Epstein-Barr Virus-positive Diffuse Large B-cell Lymphoma (EBV+DLBCL) is associated with immune dysfunction and tumor microenvironment (TME) heterogeneity. While the prognostic role of the TME in EBV-DLBCL is established, its impact on EBV+DLBCL survival remains unclear. Here, we integrated 10X Visium spatial transcriptomics (ST) with single-cell RNA sequencing (scRNA-seq) to map TME heterogeneity in EBV+DLBCL. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses identified PD-1/PD-L1 signaling as a hallmark of EBV+DLBCL’s immunosuppressive TME. Functional validation using the PD-1/PD-L1 inhibitor BMS202 revealed dose-dependent suppression of proliferation and enhanced apoptosis in EBV+Farage cells, with TLR4 emerging as a downstream effector showing EBV-status-dependent regulation. These findings not only link TME-driven PD-1/PD-L1 activation to EBV+DLBCL’s poor prognosis but also provide preclinical evidence for PD-1/PD-L1 blockade as a therapeutic strategy.